Simulating Short Gamma-Ray Burst Jets in Realistic Late Binary Neutron Star Merger Environments - Matteo Pais; Tsvi Piran; Kenta Kiuchi; Masaru Shibata (The Astrophysical Journal)
The electromagnetic emission and the afterglow observations of the binary neutron star merger event GW170817A confirmed the association of the merger with a short gamma-ray burst (GRB) harboring a narrow (5°–10°) and powerful (10 ^49 –10 ^50 erg) jet. Using the 1 s long neutrino-radiation general relativistic MHD simulation of coalescing neutron stars of K. Kiuchi et al., and following the semi-analytical estimates of M. Pais et al., we inject a narrow, powerful, unmagnetized jet into the post-merger phase. We explore different opening angles, luminosities, central engine durations, and times after the merger. We explore early (0.1 s following the merger) and late (1 s) jet launches; the latter is consistent with the time delay of ≈1.74 s observed between GW170817 and GRB 170817A. We demonstrate that the semi-analytical estimates correctly predict the jets’ breakout and collimation conditions. When comparing our synthetic afterglow light curves to the observed radio data of GW170807, we find a good agreement for a 3 × 10 ^49 erg jet launched late with an opening angle in the range ≃5°–7°.